Design and experiments of a bidirectional thyristor bridge switch for LC commutation in high-current DC vacuum circuit breaker - Meng Xu; Wei Tong; Hua Li; Zhiquan Song; Zhenhan Li; Chao Gao; Peng Fu (International Journal of Electrical Power & Energy Systems)
In the Quench Protection System (QPS) of superconducting fusion device, high-current DC breaker is an important component. LC commutation circuit provides a negative pulse current to generate zero-crossing point in Vacuum Circuit Breaker (VCB) for DC interruption. In this paper, a bidirectional thyristor bridge switch for LC commutation circuit is proposed, and the test and performance research are carried out. Firstly, the electrical issues of high-voltage stress, large-current temperature rise and voltage balancing protection are analyzed, and a 15 kV/55 kA thyristor bridge switch prototype is developed. In the testing of the prototype, the inconsistency phenomenon of series connected thyristors in trigger conducting stage was discovered. After eliminating external factors, it was found that the inconsistency was caused by the parameter dispersion of thyristors themselves. Through the selection of UGT/IGT parameter, the thyristors after replaced show higher consistency. Moreover, this phenomenon has been explained in detail based on the physical structure of thyristor. Finally, high-current experiments including pulse discharge test of LC commutation circuit and 55 kA VCB breaking test are successfully implemented. The performance of thyristor bridge switch was further verified.